FREEDOM OF SERVICES BY CORRESPONDENCE AS THE “FIFTH FREEDOM” FOR THE DIGITAL SINGLE MARKET – LIMITATIONS BY THE TFEU (EU and comparative law issues and challenges series (ECLIC), 2019)
The freedom of services by correspondence should be one of the most important market freedoms in the EU legislative politics and the CJEU jurisprudence. The announcement of the establishment of a fifth market freedom on data flow is directly addressed by the freedom of services by correspondence. The growing importance of the freedom of services in general is in line with the rise of the EU service sector as the main contributor to growth and employment in the EU, accounting for about two thirds of both EU employment and value added. In addition, since 2015 the Digital Single Market is one of European Commission’s political priority that aims at providing free access to online services. Online services are in most part services by correspondence, where neither provider nor recipient travels cross border. The truth is that the freedom of services by correspondence is barely ever mentioned explicitly neither by EU legislator nor by the CJEU. The EU legislator has rather chosen a sectoral approach to the Digital Single Market, fragmenting the fifth market freedom to several narrow pieces of legislation. The paper deals with the question why the freedom of services by correspondence has not acquired the same position as the freedom of goods. The analysis will focus on answering this question on the grounds of the theory of convergence of market freedoms and its limits.